Chewing lice from the white-rumped vulture in Nepal, with description of a new species of Aegypoecus - Shrestha, Pratichhya; Dik, Bilal; Maharjan, Mahendra (Zootaxa, 2019)
The purpose of this study was to record the species of chewing lice parasitising Gyps bengalensis (Gmelin, 1788), the white-rumped vulture, in Pithauli, Nawalparasi District, Nepal, from February to June 2017. Three louse species were identified: Cuculiphilus (Aegypiphilus) gypsis (Eichler, 1944), Colpocephalum sp., and the new species Aegypoecus bengalensis, described herein.